How do families access holiday activities and food programmes and other support? Learnings from the Borough of Southwark holiday activities and food club’s evaluation - McSweeney, Lorraine; Sewornu, Anita; Goffe, Louis; Arnott, Bronia; Adamson, Ashley (Frontiers in Public Health, 2025)
IntroductionThe school holidays can be a challenging time for many families especially for those reliant on free school meals. The Holiday Activities and Food (HAF) programme aims to provide disadvantaged families across England with healthy meals and enriching activities for children and young people. The clubs are usually in the form of a network of independent clubs and often depends on local partnerships and connections, such as the voluntary, community, social and enterprise sectors. In 2023 Southwark Council, interested in building on the findings of a national evaluation and providing more context specific insights relating to access to and use of their clubs, approached the Public Health Intervention Responsive Studies Teams scheme to collaborate in a service provision evaluation.MethodsAs part of the wider evaluation, a qualitative study was conducted. Semi-structured interviews were conducted with parents/carers of HAF eligible children and semi-structured interviews/focus groups were held with children and young people (CYP) attending a HAF club. Recruitment was through the clubs. The transcripts were coded by two independent researchers and thematic analysis applied.ResultsNine parent/carers and two young people took part in an interview. Six discussion groups with 4–6 young people in each took place. Most participants heard about the club they attended through word of mouth from friends and family, through the child’s school or by seeing a flyer/newsletter advert. Many participants were unaware of the variety and number of different clubs available to families. Finding out about the clubs online was reported to be time-consuming and websites not user-friendly. Parents/carers spoke of the frustration in trying to navigate booking systems. There was also a lack of awareness of the types of other support/signposting available from clubs.DiscussionThe evaluation highlighted the low-level of family awareness of all available HAF activities across the borough. Furthermore, navigating the system was reported as challenging. Southwark Council reviewed and revised its online provision to create a centralised repository accessible to families that aimed to improve awareness and ease the club booking process. Further work is required to improve signposting to support services and provision for parents/carers.